Pronounciation Variations: A Study on Accents and Dialects - Yani Lubis; Mutiara Sasmitha Gemilang; Amelia Azzahra; Razwa Syakira Zuhrifa Munthe (Journal of Literary and Linguistic Research, 2026)
This study investigates pronunciation variation as a fundamental dimension of linguistic diversity, focusing on the relationship between accents and dialects within sociolinguistic and phonological perspectives. Pronunciation differences are frequently shaped by phonetic processes, geographical separation, social stratification, and cultural identity formation, making them significant indicators of both linguistic and social variation. The study aims to examine the structural characteristics of pronunciation variation, particularly rhoticity and vowel shifts, while clarifying the conceptual distinction between accents and dialects. A qualitative descriptive design employing a literature review approach was used, drawing upon scholarly books, peer-reviewed journal articles, and authoritative studies in phonetics, phonology, and sociolinguistics. The findings reveal that pronunciation variation is a systematic and rule-governed linguistic phenomenon rather than a deviation from standard language norms. Accents primarily reflect differences in phonetic and phonological realization, whereas dialects encompass broader variations in lexical, grammatical, and syntactic features. The analysis further demonstrates that pronunciation patterns function as markers of social identity, cultural continuity, and community affiliation. These findings contribute to a deeper understanding of linguistic diversity and the sociocultural significance of speech variation in contemporary globalized societies.